DINAMIKA KOMUNITAS TUMBUHAN BAWAH DIHUTAN JATI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRACf Undergrowth communities in teak forests may alter due to a seasonal change from dry season to wet season and disturbances. The goals of the research were to assess the dynamics of forest undergrowth communities in a teak forest from'dry season to,wet season without any disturbances, the dynamics after the elimination of kerinyu (Eupatorium odoratum L.), and the dynamics after the eliminationof all individuals. Three plots each with a size' of 1 m x 10m were established with conditions as follows: in the first plot all plant individualswere removed, in the second plot the kerinyu population was removed, and the third plot was left intact. Data reCorded were spesies, height, and numbet